2020
DOI: 10.1155/2020/8715756
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Viruses by Multiplex Real-Time Polymerase Chain Reaction in Bronchoalveolar Lavage Fluid of Patients with Nonresponding Community-Acquired Pneumonia

Abstract: Background. Nonresponding pneumonia is responsible for the most mortality of community-acquired pneumonia (CAP). However, thus far, it is not clear whether viral infection plays an important role in the etiology of nonresponding CAP and whether there is a significant difference in the clinical characteristics between viral and nonviral nonresponding CAP. Methods. From 2016 to 2019, nonresponding CAP patients were retrospectively enrolled in our study. All patients received bronchoalveolar lavage (BAL) and viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…A retrospective study investigating the presence of respiratory viruses in bronchoalveolar lavage (BAL) samples of patients with non-responding CAP discovered an underlying viral infection in 47% of these cases, with influenza and adenoviruses as being most frequently identified pathogens. 46 There were no differences regarding clinical and laboratory data between viral or non-viral cases of nonresponding-CAP. However, the presence of ground-glass opacities combined with consolidation on CT scans was specific for viral, non-responding CAP.…”
Section: General Epidemiology and Etiology Of Severe Lvrimentioning
confidence: 81%
See 2 more Smart Citations
“…A retrospective study investigating the presence of respiratory viruses in bronchoalveolar lavage (BAL) samples of patients with non-responding CAP discovered an underlying viral infection in 47% of these cases, with influenza and adenoviruses as being most frequently identified pathogens. 46 There were no differences regarding clinical and laboratory data between viral or non-viral cases of nonresponding-CAP. However, the presence of ground-glass opacities combined with consolidation on CT scans was specific for viral, non-responding CAP.…”
Section: General Epidemiology and Etiology Of Severe Lvrimentioning
confidence: 81%
“…However, the presence of ground-glass opacities combined with consolidation on CT scans was specific for viral, non-responding CAP. 46 In the study by Shorr et al 45 viral infection was found to be significantly…”
Section: General Epidemiology and Etiology Of Severe Lvrimentioning
confidence: 93%
See 1 more Smart Citation
“…Molecular methods, such as polymerase chain reaction (PCR), are an alternative method when culture-based microbial detection methods fail. 7 , 8 However, the preselected target pathogens greatly limit the application of multiplex PCR in identifying infections caused by mixed pathogens. 9 PCR-based analyses may fail to detect unexpected, rare, or novel pathogens unless multiplexed PCRs covering all pathogenic microorganisms are employed.…”
Section: Introductionmentioning
confidence: 99%
“…Although widely used in the clinical practice, the specificity of viruses detected in the upper respiratory airways for the etiologic diagnosis of CAP remains a challenge, mostly because about 7.1% healthy people are asymptomatic carriers. 8 , 9 , 10 In addition, diagnostic samples with high specificity from lower respiratory tract (LRT) are difficult to obtain or need invasive procedures. 9 …”
Section: Introductionmentioning
confidence: 99%